PEMIKIRAN NEO ORTODOKS KARL BARTH - Abu Bakar (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
Neo-Ortodoksi is also known as " dialectic theology" to explain about Contration of Allah relationship and human being or " crisis theology" for indication that someone come up with experience with Allah [pass/through] crisis situation, The naming of neo-ortodoksi relate to " new ortodoksi" which [is] the return implication at trust of Christian of ortodoksi after almost two century take place liberalism [him/it]. In fact, the naming of that ortodoksi is not snugly, because whereas neo-ortodoksi treat Bible more serious than old liberalism, but he remain to maintain liberalism fondasiton